The status and natural history of pygmy (Kogia breviceps) and dwarf (K. sima) sperm whales off Southern Africa - Plön, Stephanie (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
For the present study 106 strandings of Kogia breviceps and 85 strandings of K. sima along the South African coastline between 1880 and 1995 were analysed in order to examine the age and growth, male and female reproduction, diet, stranding patterns, and population genetic structure of both species. Length and weight at birth were about 120cm and 53kg for K. breviceps and about 103cm and 14kg for K. sima. Von Bertalanffy growth curves were fitted to the data and indicated that physical maturity was reached at around 15 years in both sexes of K. breviceps and at 13 years in female and 15 years in male K. sima. Asymptotic length was reached at 306.0 and 286.1cm in female and male K. breviceps and 249.14 and 263.75cm in female and male K. sima, respectively. Maximum ages were16 years for male K. breviceps and 23 years for females and 17 years for male K. sima and 22 years for females. Reversed sexual size dimorphism was suggested for K. breviceps, while in K. sima males were larger than females. Attainment of sexual maturity in males occurred at between 2.5 and 5 years of age in K. breviceps and 2.6 and 3 years in K. sima, corresponding to 241-242cm and 197cm body length, respectively. The maximum combined testis weight comprised 1.04% and 2.00% for K. breviceps and K. sima, respectively, and a polygynous mating system with a roving male strategy was proposed for both species. The sperm morphology for both Kogia species was described and is characterised by 20-25 spherical mitochondria arranged in rows around the midpiece. Attainment of sexual maturity in females occurred at 5 years in both Kogia species, and at 262cm and 215cm body length in K. breviceps and K. sima, respectively. The ovulation rates were 0.9 and 0.7 per year for K. breviceps and K. sima, respectively. In K. breviceps conceptions occurred from April to September and births from March to August, while in K. sima both conceptions and births occurred from December to March. Annual reproduction and a post-partum oestrus was suggested for both Kogia species. The diet of K. breviceps comprised 50 different cephalopod species from 22 families and 17 other prey species, while K. sima fed on 32 cephalopod species from 17 families and six others. Although niche overlap indices between the two species and between groups within each species were high, some differences in diet could be determined, which allow these two sympatrically occurring species to share the same ecological niche off the coast of Southern Africa. An analysis of the stranding patterns revealed that K. sima has a closer affinity to the Agulhas current and to higher water temperatures than K. breviceps, which is supported by differences in the size of the appendages between the two species. The population genetic analysis revealed a high haplotype and nucleotide diversity for K. breviceps in the Southern hemisphere, but a lack of significant phylogeographic structure, indicating substantial gene flow among populations and inhibiting genetic differentiation of local populations, although the South African population was somewhat isolated from others in the Southern Hemisphere. In contrast the data on the phylogeographic structure of K. sima were somewhat restrictive as the majority of the samples originated from South Africa. Nevertheless, both nucleotide and haplotype diversities were markedly lower than in K. breviceps and more similar to those for other small cetacean populations, suggesting a smaller population size for K. sima than for K. breviceps. Although both Kogia species belong to the medium to larger-sized odontocetes their life histories are located near the fast end of the slow-fast continuum of life histories of marine mammals, indicating high mortality rates. The "false-gill" marking and the ability to squirt ink are thought to reflect adaptations to predator mimicry and avoidance.
Keywords: Pygmy sperm whale; Dwarf sperm whale; Population genetics